Clima organizacional en la Caja Trujillo de Huamachuco. - Villa Saez, Milagros Celinda (2011)
The human being is a creature composed of hunger and complexity because of emotions that occur in their environment, which will affect them directly. If he feels that his environment is good, the acting is going to be in this way, but if his environment is unfavorable his performance will also decrease. The environment can be external, the environment surrounding it, but it can also be internal, and an example of a close environment is the home and the workplace. Therefore, the circumstances of their work will determine their behavior in terms of performance and productivity in the work. The circumstances of their work affect their performance and productivity, so the present investigation seeks to determine how environment at the workplace affects productivity of Caja Trujillo – Huamachuco´s workers, whichs is an important financial institution that contributes to regional development. If the working environment is not the optimal, productivity is neither; in this case the number of new credits given would decrease and the arrears would increase, but instead if the environment is the optimal the productivity an the number of new credits will also be increased and the arrears would be reduced. Finally, we intend to propose alternative solutions to help to improve the organizational climate and thus increase the productivity of the Caja Trujillo - Huamachuco and contribute to positioning and organizational growth.